Understanding Indonesia: the Role of Economic Nationalism - Thee Kian Wie (Journal of Indonesian Social Sciences and Humanities, 2010)
In this paper it is argued that economic nationalism in Indonesia, in its various manifestations, has been an important factor in determining particular economic policies since Indonesias independence up to the present. These economic policies particularly related to the ownership of productive assets owned by foreigners or by residents considered to be foreign, particularly Dutch business interests before 1957 and the ethnic Chinese, including Sino-Indonesians, and to the economic functions performed by foreigners or by foreign residents. Focusing on one factor alone to understand Indonesia, specifcally Indonesias economic policies over time, is necessarily arbitrary and subjective. However, looking at Indonesias modern economic history since independence through the prism of economic nationalism does to an important degree explain or highlight the major considerations underlying particular economic policies of the Indonesian government because they rejected Indonesias national aspirations or national interests.